Based Internal Auditing and Financial Transparency among Fintech Companies: JEL Classification: M42; G23; G28; O33; D83 - Siti Khodijah Ismail; Aisyah Zulkifli (Generasi Sains Indonesia, 2026)
This study aims to analyze the influence of AI-based internal auditing on financial transparency among FinTech companies in Malaysia. The increasing complexity of digital financial systems and the growing demand for transparent financial governance have intensified the importance of intelligent auditing technologies within modern financial institutions. This research employed a quantitative explanatory approach using survey data collected from 187 respondents working in Malaysian FinTech companies, including internal auditors, financial managers, compliance officers, and operational staff. Data were analyzed using descriptive statistics, validity and reliability testing, correlation analysis, and multiple linear regression. The findings demonstrate that AI-based internal auditing has a positive and statistically significant effect on financial transparency. Fraud detection emerged as the strongest dimension of AI auditing implementation, while reporting accuracy represented the most dominant dimension of financial transparency. The study further reveals that AI-driven auditing systems improve accountability, strengthen financial reporting reliability, and support more effective governance practices within digital financial environments. The findings provide theoretical contributions to digital auditing literature and practical implications for regulators and FinTech companies in developing more transparent and accountable financial governance systems.